ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PT ELNUSA TBK PERIODE 2019-2021 - Maria Anziana Bone; Agus Riyanto; Nadya Yunan (University of Widya Gama Mahakam Samarinda, 2023)
The purpose of this study is to determine the financial performance of PT Elnusa Tbk for the 2019-2021 period in terms of financial ratios consisting of Liquidity Ratios, Solvency Ratios, Activity Ratios, Profitability Ratios, and Market Ratios. The method used in this research is descriptive quantitative. The data used in this study are PT Elnusa Tbk's Financial Position Report and Profit and Loss Report for the 2019-2021 period. Based on the research results, it is known that the value of the Liquidity Ratio shows that the ratio results are above the industry average standard. Solvability ratios show results below the industry average standard. The activity ratio shows that the results are below the industry average standard. Profitability ratios show results below the industry average standard. Market Ratio shows results above the industry average standard.